Quality provision and reporting when health care services are multi-dimensional and quality signals imperfect - Katharina Huesmann; Wanda Mimra (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
We model competition for a multi-attribute health service where patients observe attribute quality imprecisely before deciding on a provider. High quality in one attribute, e.g. medical quality, is more important for ex post utility than high quality in the other attribute. Providers can shift resources to increase expected quality in some attribute. Patients rationally focus on attributes depending on signal precision and beliefs about the providers' resource allocations. When signal precision is such that patients focus on the less important attribute, any Perfect Bayesian Nash Equilibrium is inefficient. Increasing signal precision can reduce welfare, as the positive effect of better provider selection is overcompensated by the negative effect that a shift in patient focusing has on provider quality choice. We discuss the providers' strategic reporting incentives and reporting policies. Under optimal reporting, signals about the important attribute are always published. However, banning reporting on less important attributes might be necessary.
Keywords: I11; D83; L10; 330; multi-attribute good; quality signals; focusing; reporting